Targeting Endocannabinoid Signaling in the Lateral Habenula as an Intervention to Prevent Mental Illnesses Following Early Life Stress: A Perspective - Shepard, Ryan D.; Nugent, Fereshteh S. (Frontiers in Synaptic Neuroscience, 2021)
Adverse events and childhood trauma increase the susceptibility towards developing psychiatric disorders (substance use disorder, anxiety, depression, etc.) in adulthood. Although there are treatment strategies that have utility in combating these psychiatric disorders, little attention is placed on how to therapeutically intervene in children exposed to early life stress (ELS) to prevent the development of later psychopathology. The lateral habenula (LHb) has been a topic of extensive investigation in mental health disorders due to its prominent role in emotion and mood regulation through modulation of brain reward and motivational neural circuits. Importantly, rodent models of ELS have been shown to promote LHb dysfunction. Moreover, one of the potential mechanisms contributing to LHb neuronal and synaptic dysfunction involves endocannabinoid (eCB) signaling, which has been observed to critically regulate emotion/mood and motivation. Many pre-clinical studies targeting eCB signaling suggest that this neuromodulatory system could be exploited as an intervention therapy to halt maladaptive processes that promote dysfunction in reward and motivational neural circuits involving the LHb. In this perspective, we report what is currently known about the role of eCB signaling in LHb function and discuss our opinions on new research directions to determine whether the eCB system is a potentially attractive therapeutic intervention for the prevention and/or treatment of ELS-associated psychiatric illnesses.